Coronavirus e ambiente: una sfida per il pianeta e per la salute - Cristiano Magnaghi; Elena Brioni; Donato Leopaldi; Marisa Pegoraro; Giuseppe Vezzoli; Paolo Manunta; Maria Teresa Parisotto (AboutScience Srl, 2020)
In late December 2019, some patients were hospitalized with an initial diagnosis of pneumonia of unknown etiology. These patients were epidemiologically linked to a wholesale market of seafood, wild animals and meat located in Wuhan, Hubei province, China. Acute respiratory disease caused by a new Coronavirus SARS-CoV-2, formerly known as 2019-nCoV, afterwards as Coronavirus disease 2019 (COVID-19), spread throughout China and received the attention of the entire world. Analysis of the genomic sequence of COVID-19 showed 88% of identity with two bat-derived severe acute respiratory syndrome-like Coronaviruses. Illegal and sustainable wildlife trade is the second largest direct threat to species after habitat destruction. Each year, hundreds of millions of plants and animals are captured or collected in the wild to be sold as food, pets, medicines, ornaments and for a variety of other reasons. Even the climate crisis could offer dangerous scenarios in addition to another fundamental chapter of the environmental pillar which is the one concerning air quality. There is a solid scientific literature which correlates the incidence of viral infection cases with concentrations of atmospheric particulate matter (e.g. PM10 and PM2.5). Despite the current regulations, which limit the levels of certain atmospheric pollutants, there are still numerous negative health effects deriving from exposure to these agents. However, it can be said that chronic air pollution, such as peaks of concentration of fine dust and other pollutants, acts as a pejorative factor in cases of epidemics. (GCND_planet)